Well g(x) basically just means that a function, called g(x) in this case, is equal to x^2-4.So ignore g(x) and just concentrate on what it says on the right side og the equation. We can use the rule (a - b)(a + b) = (a^2 - b^2). In your case a = x and b = 2 as sqrt.4 = 2. So from this we see that:x^2 - 4 = (x - 2)(x + 2)So, now you've got the two factors of g(x). If you afterwards want to find the factors for g(0) or another value for x, you just put it into the equation. Hope this helped and that it was what you were asking for.